German Administrative Judiciary: Features of a Specific System - Radošević, Ratko S. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
Features of the German administrative judiciary are the subject of this paper. The paper is divided into several parts. In the first part, origins and development of the German administrative judiciary are explained, so that the historical background of the current system could be fully grasped. The next part is about the position and the organisation of the German administrative judiciary, which is considered to be a special and separated branch of judiciary. The following topic makes the very essence and the spirit of the German administrative judiciary – the idea of the comprehensive legal protection of parties in their legal relations to the public administration, as a state power and authority. Finally, the explanation is being finished with the administrative courts procedure and it includes its general principles, civil law origins and its subtle relation to the administrative procedure.